ANALISIS SISTEM REKRUTMEN DAN PELATIHAN DALAM MENINGKATKAN KINERJA KARYAWAN - Siyah Siyah; Mansur Mansur; Ridan Muhtadi (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2020)
Introduction: Sharia financial institutions, especially SPM Pamekasan Sharia Banks, in carrying out each of their operational activietis must depend on human resources (HR) as managers in every company activity. Therefore, SPM Pamekasan Sharia Bank must place human resources (employees) according to their field capabilities. The research here aims to be able to find out how the recruitment and training system is carried out in the SPM Pamekasan Sharia Bank and how the performance of employees using both systems. Methods: The research method used by researchers, namely using descriptive qualitative methods, using data collection techniques in the form of observation, interviews, and documentation. Results: The results of this study the recruitment system implemented by the SPM Pamekasan Sharia Bank uses two systems, namely internal and external recruitment and both recruitment systems are said to be quite good. For the training system implemented by the SPM Pamekasan Sharia Bank, namely an external and internal training system. Of the two recruitment and training systems carried out by Bank Syariah SPM Pamekasan have a positive effect on employee performance. This can be seen from the increase in employee performance appraisal of the SPM Pamekasan Syariah Bank which increased in 2019 compared to 2018. Keywords: Recruitment System, Training, Employee Performance.